POLA INTERAKSI VERBAL GURU BIOLOGI SETELAH MENDAPATKAN PELATIHAN KURIKULUM 2013 - Abdan Albirron; Yanti Herlanti; Dina Rahma Fadlilah (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2019)
VERBAL INTERACTION CATEGORY SYSTEM OF 2013 CURRICULUM BIOLOGY TEACHER TRAINED AbstractPrevious research has shown that the implementation of Curriculum 2013 has success. However, it is not objective yet. This descriptive research aims to describe the pattern of verbal interaction during the learning process in class XI MIA. The research was conducted in 3 High Schools of Bogor City that implemented the Curriculum 2013. The matrix of Flander’s Verbal Interaction Category System (VICS) instrument was used to analyze interaction beetween teacher and students. The result of the study is the learning process in the three student-centered schools with the students multi-direction interaction patterns about 47,19% in School A, 74,37% in School B, and 70,77% in School.AbstrakPenelitian sebelumnya telah menunjukkan bahwa implementasi Kurikulum 2013 telah berhasil. Namun, itu belum objektif. Penelitian deskriptif ini bertujuan untuk mendeskripsikan pola interaksi verbal selama proses pembelajaran di kelas XI MIA. Penelitian ini dilakukan di 3 SMA Kota Bogor yang menerapkan Kurikulum 2013. Matriks instrumen Sistem Interaksi Verbal Kategori Belgia (VICS) digunakan untuk menganalisis interaksi antara guru dan siswa. Hasil dari penelitian ini adalah proses pembelajaran di tiga sekolah yang berpusat pada siswa dengan pola interaksi multi-arah siswa sekitar 47,19% di Sekolah A, 74,37% di Sekolah B, dan 70,77% di Sekolah C.